Tic's y su aporte en los procesos administrativos en las secretarias del departamento de talento humano del subcentro de salud pública de la parroquia Antonio Sotomayor, cantón Vinces - Rojas Macias, Sonnia Betzaida (2021)
The present case study entitled Tic's and its contribution to the administrative processes in the secretaries of the human talent department of the public health sub-center of the Antonio Sotomayor parish of Canton Vinces, This is a public institution dedicated to providing medical care to a community in general , which through different research techniques will detect the shortcomings that mainly affect the area of human talent, to indicate a progressive advance in the subject, the deductive method was used because it allows focusing the information from the particular to the general, the Data collection technique was the survey that was very useful to obtain all the information that we have to complete this research work, in addition to detailing what the internal work is like and how the administrative processes are applied. The results finally revealed that secretaries are not applying tic's in administrative processes since they still use old work tools and techniques that slow down activities in the area, affecting other departments, so that this does not continue to happen, the final recommendations were to create a detailed planning of the latest work done by the department and thus detect errors that affect daily activities, as well as the pertinent authorities requesting annual training on the use and benefits of ICTs to all the institution's personnel.